Thermal analysis in structural characterization of hydrazone ligands and their complexes - Andjelkovic, K.; Sumar, Maja; Ivanovic-Burmazovic, Ivana (Journal of Thermal Analysis and Calorimetry, 2001)
Results of our research on synthesis and characterization of complexes with acylhydrazone derivatives are described in this review paper. Structural characterization of newly synthesized complexes by thermal analysis (TG, DTA, DSC) is particularly emphasized in this paper. Thermal analysis enabled us to study not only structural changes of substances during thermal treatment, but also the mode of coordination and degree of deprotonation of acylhydrazones, as well as geometry of the coordination sphere of complexes, the structure of which had not been determined by X-ray analysis. Topics in this paper are as follows: complexes of dioxomolybdenum(VI) with tridentate hydrazones, usnic acid derivatives and their Cu(II) complexes, as well as transition metal complexes with 2,6-diacetylpyridine bis(hydrazones).